Do Insiders Learn from Outsiders? Evidence from Mergers and Acquisitions - LUO, YUANZHI (Journal of Finance, 2005)
ABSTRACT I find that the market reaction to a merger and acquisition (M&A) announcement predicts whether the companies later consummate the deal. The relation cannot be explained by the market's anticipation of the closing decision or its perception of the deal quality at the announcement. Merging companies appear to extract information from the market reaction and later consider it in closing the deal. Furthermore, the relation varies with deal characteristics, suggesting that companies seem to have a higher incentive to learn from the market when canceling the announced deal is easier or when the market has more information that the companies do not know.